2004
DOI: 10.1117/12.552523
|View full text |Cite
|
Sign up to set email alerts
|

Modeling tools to estimate the performance of the Thirty Meter Telescope: an integrated approach

Abstract: A sound system engineering approach and the appropriate tools to support it are essential in achieving the scientific and financial objectives of the Thirty Meter Telescope project. Major elements of the required tool set are those providing estimates for the performance of the telescope. During the last couple of years, the partners in the consortium developed a wide range of modeling and simulation tools with various levels of fidelity and flexibility. There are models available for time domain and frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Currently, the integrated modeling tools from HIA as well as those developed by AURA and Caltech are being used to assess the performance of telescope structural designs for TMT 25,26 .…”
Section: Figure 12 -Optical Modeling Toolsmentioning
confidence: 99%
“…Currently, the integrated modeling tools from HIA as well as those developed by AURA and Caltech are being used to assess the performance of telescope structural designs for TMT 25,26 .…”
Section: Figure 12 -Optical Modeling Toolsmentioning
confidence: 99%
“…Pressure signals collected at different points on the mirror surface showed that the wind pressure load at low frequencies was www.intechopen.com reduced by the building; however, the high frequency wind pressure components increased under these conditions. Angeli et al (2004) presented an integrated approach for the necessary modeling tools to estimate the performance of the TMT, which is an upgraded version of the VLOT. Among these tools, the authors emphasized the role of CFD in predicting the wind loading and buffeting, which are more crucial during the conceptual design phase of the telescope.…”
Section: Review Of Flow Simulations On Large Telescopesmentioning
confidence: 99%
“…However, with the aperture open, the residual wind loads resulting from large scale flow structures and turbulence inside the telescope enclosure may still lead to significant vibration that must be taken into account in the design of future large telescopes (Padin and Davison, 2004;Angeli et al, 2004;MacMynowski et al, 2004), affecting the design of the enclosure, the structure and the control system. To estimate the resulting image degradation with sufficient confidence for design, a better understanding of the wind inside the telescope enclosure is required.…”
Section: Introductionmentioning
confidence: 99%